Original drugs approved by the Food and Drug Administration (Center for Drug Evaluation and Research) in 2024 - D. V. Kurkin; N. A. Osadchenko; A. R. Makarova; D. A. Galkina; D. A. Bakulin; O. V. Shatalova; A. V. Strygin; V. I. Petrov; O. V. Marincheva; Yu. V. Gorbunova; Yu. A. Kolosov; A. V. Zaborovsky; et al. (Фармация и фармакология (Пятигорск), 2025)
The U.S. Food and Drug Administration (FDA), in particular the Center for Drug Evaluation and Research (CDER), plays a key role in ensuring the safety, efficacy, and innovation of medicines entering the U.S. market, and then the world. The annual review of new medicines approved by the FDA is an important tool for analyzing current trends in pharmacology and medicine, reflecting progress in the treatment of complex diseases, including cancers, orphan diseases, and infections. The review is compiled to familiarize medical specialists and pharmacologists with current trends in the registration of original medicines and in the therapy of malignant neoplasms, orphan diseases.The aim. To summarize and systematize data on the newest medicines that entered the market in 2024, as well as to analyze the mechanisms of their action. The article aims to inform medical specialists and pharmacologists about current trends in the development and registration of innovative medicines in 2024.Materials and methods. The presented data are taken from open sources and supplemented with the results of individual studies on new mechanisms and approaches in therapy. The main list of new drugs and introductory information about them are taken from the FDA report “Novel Drug Approvals for 2024”. Data on medicine prescriptions, as well as information on the mechanism of action, are taken from published summary of product characteristics (SmPC) published on this resource, as well as from the Drugs.com website. To describe previously registered medicines for which a new indication is presented, Drugs.com reports were also used. Structural formulas of drugs are taken from the PubChem resource. In case of the absence of structural formula, data from their SmPC or third-party resources, such as Drugbank, were used. The search for literature data on fundamental studies relating to the mechanisms of action of the presented medicines was carried out in the PubMed, ResearchGate, Google Scholar and elibrary.ru databases.Results. A statistical analysis of registrations, the dynamics of changes in the shares of various types of medicines and basic data on new original drugs registered by CDER are presented. In 2024, the FDA registered 50 original medicines, among which 48% contain a “first-in-class” molecule as an active substance. Small molecules include active substances — 60%, and biopharmaceuticals — 34% (the remaining 6% are imaging agents). At the same time, monoclonal antibodies (mAb) of antitumor and anti-inflammatory action occupy a larger share among biopharmaceuticals.Conclusion. The large proportion of biopharmaceuticals among those newly registered in 2024 emphasizes the dynamic development of the pharmaceutical industry and its focus on personalized medicine and biotechnology. Therapy based on mAbs interacting with receptors, as well as immunotherapy based on newly discovered mechanisms of antitumor immunity, occupies a separate part in the structure of registered original medicines. The search for new rational combinations of antibiotics remains relevant. Most of the original drug market is still made up of small molecules, among which there are medicines — ligands of new targets and oligonucleotide sequences.